Clinical Outcomes and Prognostic Factors for Patients with Malignant Peripheral Nerve Sheath Tumour. (24th November 2021) - Imura, Yoshinori; Outani, Hidetatsu; Takenaka, Satoshi; Yasuda, Naohiro; Nakai, Sho; Nakai, Takaaki; Wakamatsu, Toru; Tamiya, Hironari; Hamada, Kenichiro; Kakunaga, Shigeki
Abstract : Introduction . Few studies have described the characteristics and prognostic factors of patients with malignant peripheral nerve sheath tumour (MPNST). In this study, we retrospectively investigated the clinicopathological features, clinical outcomes, and prognostic factors of these patients. Patients and Methods . We recruited patients with MPNST who were treated at our institutions from 1991 to 2020. We collected and statistically analysed information on patient-, tumour-, and treatment-related factors. The median follow-up period was 61 months (range, 1–335.8 months). Results . A total of 60 patients (31 males, 29 females) with a median age of 55 years (range, 8–84 years) at initial diagnosis were included. The median tumour size was 7 cm (range, 1.6–30 cm) in the greatest dimension. The 5-year overall survival (OS) rate of all patients was 69.5%. Univariate analysis revealed that large-sized tumour, metastasis at diagnosis, and no surgery of the primary tumour were significantly associated with patients with worse OS. Multivariate analysis identified surgery of the primary tumour as an independent prognostic factor for improved OS. Among patients with localised disease at diagnosis who underwent surgery of the primary tumour at our institutions, the 5-year OS, local recurrence-free survival (LRFS), and metastasis-free survival (MFS) rates were 81.1%, 78.2%, and 70.3%, respectively. Univariate analysis revealed that positive surgical margin was significantly correlated with unfavourable OS and LRFS, and high grade was a poor prognostic indicator for MFS. Conclusion . Complete surgical resection with negative surgical margins is necessary for a successful MPNST treatment. Multidisciplinary management of MPNST with aggressive features is important for optimising patient outcomes.